PENGARUH KEPEMIMPINAN DEMOKRATIS DAN KOMUNIKASI TERHADAP KINERJA PADA KANTOR KESATUAN BANGSA DAN POLITIK KOTA SIBOLGA - Cindi Cisilya Angeline Situmeang; Kaharuddin; Sriayu Aritha Panggabean (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to determine whether there is an influence of democratic leadership and communication on performance in national unity and politics in the city of Sibolga. The type of research used in this research is descriptive quantitative. The sample in this study were employees at the Office of National Unity and Politics in the City of Sibolga with a total of 32 respondents distributing questionnaires. Based on the results of the study, it showed that there was a positive relationship between democratic leadership and performance at the Office of National Unity and Politics in the City of Sibolga, which was 0.093, while communication with employee performance was 0.123 so that when interpreted on a value scale it could be categorized as sufficient and good. The regression equation obtained is Y = 39.446 + 0.037X1 + 0.161X2 which shows leadership and communication on performance. The t test shows that the proposed hypothesis is rejected, where t count is -0.111 <2.04227 which means that employee performance will decrease by the regression coefficient (0.100) if the democratic leadership variable is added to one unit and other variables are considered constant. While communication has a significant effect on employee performance where t count < t table, namely -0.111 <2.04227. While the coefficient of determination is known that free-control democratic leadership only plays a role of 0.100% of the performance at the Office of National Unity and Politics in Sibolga City and the rest is influenced by factors not examined.